Fast-kz three-dimensional tailored radiofrequency pulse for reduced B1 inhomogeneity - Suwit Saekho (2018)
This article presents a small-flip-angle, three-dimensional tailored RF pulse that excites thin slices with an adjustable quadratic in-plane spatial variation. The quadratic spatial variation helps to compensate for the loss in image uniformity using a volume coil at 3 T due to the wavelike properties of the RF field. The pulse is based on a novel "fast-kz" design that uses a series of slice-select subpulses along kz and phase encoding "blips" along kx-ky. The method is demonstrated by acquiring a series of 5-mm-thick T2-weighted images of the human brain at 3 T using pulses 4.8 ms in length with a 45 ° flip angle. © 2006 Wiley-Liss, Inc.